Balint groups as a method to prevent stress in mental health workers - Avagimyan, Anzhela A.; Krasnyuk, Ivan I.; Kasimovskaya, Nataliya A.; Ulianova, Nina A.; Pryazhnikova, Elena Y.; Matanis, Victoria A. (Opción, 2020)
The article focuses on the analysis and correction of professional burnout in mid-level health workers of No. 3 V.A. GILYAROVSKY Psychiatric Hospital, Moscow Healthcare Department. The article reviews indicators of professional deformation and describes Balint group work as a method of prevention of professional burnout. Growing age brings increased professional experience, but also professional deformation, rendering the work to overcome it necessary. Based on global experience and our own observations, we recommend Balint groups as a long-term program for correction of professional burnout in nurses. Our study proved them effective in forming a positive professional culture.